2022
DOI: 10.1002/fft2.169
|View full text |Cite
|
Sign up to set email alerts
|

Citri Reticulatae Pericarpium extract and flavonoids reduce inflammation in RAW 264.7 macrophages by inactivation of MAPK and NF‐κB pathways

Abstract: Citri reticulatae Pericarpium (CRP) is widely consumed as a food and herbal medicine in various countries and has many biological activities, including anti-inflammatory effects, but the molecular mechanism is not completely known. This study aims to investigate whether CRP extract and its major flavonoids hesperidin (Hsd) and hesperetin (Hst) can reduce inflammation in macrophages and the underlying mechanism.The chemical composition of CRP was detected by ultra-performance liquid chromatography-mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Under basal conditions, NF-κB is arrested in the cytoplasm, remaining inactivated, and cannot bind to the nuclear DNA consensus sequence to initiate inflammation-related transcriptional processes, including the rapid expression of several proinflammatory cytokines, such as IL-6, IL-1α/β, and TNFα. 43,44 These findings support our study, indicating that lycopene could attenuate E. coli-induced inflammation by inactivating NF-κB, resulting in a reduced expression of proinflammatory cytokines, including IL-6, IL-1α/β, and TNFα. TLR-4 can activate the NF-κB pathway and the secretion of inflammatory cytokines; 45 these proinflammatory cytokines can interact with NF-κB to accelerate inflammation.…”
Section: ■ Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Under basal conditions, NF-κB is arrested in the cytoplasm, remaining inactivated, and cannot bind to the nuclear DNA consensus sequence to initiate inflammation-related transcriptional processes, including the rapid expression of several proinflammatory cytokines, such as IL-6, IL-1α/β, and TNFα. 43,44 These findings support our study, indicating that lycopene could attenuate E. coli-induced inflammation by inactivating NF-κB, resulting in a reduced expression of proinflammatory cytokines, including IL-6, IL-1α/β, and TNFα. TLR-4 can activate the NF-κB pathway and the secretion of inflammatory cytokines; 45 these proinflammatory cytokines can interact with NF-κB to accelerate inflammation.…”
Section: ■ Discussionsupporting
confidence: 86%
“…NF-κB is a well-known regulator of innate immunity and can be activated by inflammatory media, like cytokines and receptors responsive to bacterial infection, such as Toll-like receptors (TLRs). Under basal conditions, NF-κB is arrested in the cytoplasm, remaining inactivated, and cannot bind to the nuclear DNA consensus sequence to initiate inflammation-related transcriptional processes, including the rapid expression of several proinflammatory cytokines, such as IL-6 , IL-1α / β , and TNFα . , These findings support our study, indicating that lycopene could attenuate E. coli-induced inflammation by inactivating NF-κB, resulting in a reduced expression of proinflammatory cytokines, including IL-6 , IL-1α / β , and TNFα .…”
Section: Discussionsupporting
confidence: 84%
“…11 In addition, roots of Codonopsis pilosula, Pericarpium Citri Reticulatae, Spathodea campanulata, Angelica sinensis, and Atractylodes macrocephala also exerts anti-inflammatory activity. [12][13][14][15][16] This effect contributes to the treatment of hemorrhoids. In summary, the findings of this study indicated "TRI 01" hard capsule showed some beneficial effects on croton oil-induced hemorrhoids and validates its ethnomedicinal use in treatment of piles.…”
Section: Discussionmentioning
confidence: 99%
“…The extract acted on all three MAPK signaling pathways to reverse LPS-induced phosphorylation of JNK, ERK1/2, and p38 MAPK. Furthermore, the extract could inhibit the NF-κB signaling pathway by reducing the phosphorylation of NF-κB p65 ( 44 ).…”
Section: Plant-based Functional Foods Exert Anti-inflammatory Effectsmentioning
confidence: 99%